Efficacy and safety of metformin in combination with chemotherapy in cancer patients without diabetes: systematic review and meta-analysis - Yang, Kang; Lu, Hao-hao; Zhao, Wei; Zhao, Qingchun (Frontiers in Oncology, 2023)
The results of a meta-analysis of retrospective studies suggest that the use of metformin in cancer patients may prolong progression-free disease survival and overall survival. However, the studies included in the meta-analysis did not strictly distinguish between patients with or without type 2 diabetes mellitus. Therefore, further studies are needed to assess whether the use of adjuvant chemotherapy with metformin in cancer patients without diabetes improves prognosis. Method: Systematic searches of Embase, Pubmed, and The Cochrane library were performed for the subject terms metformin and neoplasm and for free words. Data related to PFS, OS were extracted according to inclusion exclusion criteria. The data were combined and meta-analysis was performed using Rrvman 5.4 to confirm the efficacy and safety of metformin administration. Results:There were 3228 publications retrieved from the database and a total of 13 publications with 955 patients were included in the meta-analysis after screening. All included studies were randomised controlled trials. Metformin combined with adjuvant chemotherapy did not improve progression-free survival (HR=1,95CI 0.79~1.25) ， overall survival (HR=0.91,95% CI 0.69~1.20) and did not improve objective disease response rates in patients. There was no significant difference in grade 3-4 adverse reactions compared to placebo. Conclusions: In this meta-analysis of randomised controlled trial studies, we found that chemotherapy in combination with metformin in cancer patients without diabetes did not prolong progression-free survival and overall survival and improved disease control in patients, although there was no significant difference in terms of safety. More high-quality randomised controlled trials are needed in the future to confirm the in vivo anti-tumour activity and survival benefit of metformin.